2019
DOI: 10.2196/10039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality and Differences in Stress Processing Among Finnish Students on Interest to Use a Mobile Stress Management App: Survey Study

Abstract: BackgroundExcessive stress has a negative impact on many aspects of life for both individuals and societies, from studying and working to health and well-being. Each individual has their unique level of stress-proneness, and positive or negative outcomes of stress may be affected by it. Technology-aided interventions have potential efficacy in the self-management of stress. However, current Web-based or mobile stress management solutions may not reach the individuals that would need them the most, that is, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 48 publications
6
38
0
1
Order By: Relevance
“…Furthermore, personal relevance and mental health needs may affect the acceptance of mHealth apps; therefore, public health initiatives on mHealth could highlight the benefits of preventive innovations that tend to diffuse very slowly (delay of reward after adoption), as proposed by Rogers [108]. Although our results correspond to findings on the relationship between stress and interest in using mHealth for stress management [75], it is important to mention that self-reported stress severity in our sample was low to moderate. Considering that the main target group for primary prevention and health promotion in Germany is healthy adults [109], such apps may have the highest potential to reach populations that are already rather privileged in terms of having the necessary resources and knowledge to efficiently use mental health services, as was the case in our sample.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, personal relevance and mental health needs may affect the acceptance of mHealth apps; therefore, public health initiatives on mHealth could highlight the benefits of preventive innovations that tend to diffuse very slowly (delay of reward after adoption), as proposed by Rogers [108]. Although our results correspond to findings on the relationship between stress and interest in using mHealth for stress management [75], it is important to mention that self-reported stress severity in our sample was low to moderate. Considering that the main target group for primary prevention and health promotion in Germany is healthy adults [109], such apps may have the highest potential to reach populations that are already rather privileged in terms of having the necessary resources and knowledge to efficiently use mental health services, as was the case in our sample.…”
Section: Discussionsupporting
confidence: 76%
“…Remarkably, the motivating influence of current needs (eg, for support in stressful situations) on intentions to use e-mental health services has not been consistently clarified. On the one hand, there is evidence for an association between stress perceptions and attitudes toward using e-mental health treatments [33,74] and a higher interest in using stress management apps [75]. On the other hand, there is evidence for “digital stress” caused by online multitasking and overload (eg, [76]).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
“…In the study by Vujičić and Ranđelović (2017) it was found the same results but it was not found the stress correlation. However, Ervasti et al (2019) found that agreeableness negatively correlated to self-reported stress. In addition, Mousavi and Essazadegan (2016) indicated that anxiety and depression negatively correlated with agreeableness.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation